Innate Rhythms: Clocks at the Center of Monocyte and Macrophage Function - Timmons, George A.; O'Siorain, James R.; Kennedy, Oran D.; Curtis, Annie M.; Early, James O. (Frontiers in Immunology, 2020)
The circadian cycle allows organisms to track external time of day and predict/respond to changes in the external environment. In higher order organisms, circadian rhythmicity is a central feature of innate and adaptive immunity. We focus on the role of the molecular clock and circadian rhythmicity specifically in monocytes and macrophages of the innate immune system. These cells display rhythmicity in their internal functions, such as metabolism and inflammatory mediator production as well as their external functions in pathogen sensing, phagocytosis and migration. These inflammatory mediators are of clinical interest as many are therapeutic targets in chronic inflammatory disease such as cardiovascular disease, diabetes and rheumatoid arthritis. Moreover, circadian rhythm disruption is closely linked with increased prevalence of these conditions. Therefore, understanding the mechanisms by which circadian disruption affects monocyte/macrophage function will provide insights into novel therapeutic opportunities for these chronic inflammatory diseases.